PENANGANAN PEMUKIMAN KUMUH, STUDI KASUS KELURAHAN OESAPA, KECAMATAN KELAPA LIMA KOTA KUPANG - Djati, Arifa Aini. A; Wulakada, Hamza Huri; Rahmawati, Arfita (Universitas Nusa Cendana, 2023)
This study aims to analyze the level of slums and handling the slum settlements in the Oesapa village, Kelapa Lima sub-district, Kupang city. The type of research used quantitative research. Interview data collection techniques, documentation studies, observation. This research was conducted in December 2022. The results showed that: (1) the level of slums in Oesapa Village on indicators of building conditions and waste management is that Oesapa Village is in the moderate slum stage. (2) the KOTAKU program has influence on the management of slum settlements in Oesapa Barat Village through indicators of waste management and building conditions, although it has not yet had a large-scale impact on the local environment. The government's communication with the community needs to be improved in this case, every City Without Slums (KOTAKU) program must be well socialized so the all people know about the KOTAKU program being implemented and there is a need for equitable counseling in the Oesapa Village regarding the KOTAKU program (3) In terms of handling slums in the Oesapa Village through the KOTAKU program the concept of developing coastal tourism development areas, preserving mangrove ecosystems and developing mangrove ecotourism, developing environment- based economies that support the development of waterfront cities.